The Impact of a Proposed Physical and Sports Program on Lipid Ratio for Type 2 Diabetes Patients - Khireddin, Boukria; Benkara, Yassine; Gasmi, Abdelmalek; Mohammed, Khellaf; Fouad, Chiha; Benlabed, Abderrahim (Journal of Neonatal Surgery, 2025)
The aim of this study was to investigate the impact of a proposed physical and sports programme on the lipid ratio of type 2 diabetes patients. In this study we adopted an experimental approach, and the sample consisted of 15 patients with type 2 diabetes; the study consisted of a ‘pre-test-post-test’ experimental investigation. This investigation was interested in measuring the lipid ratio before and after the physical and sports programme, which was designed and implemented over a 12-week period. The equipment used was in line with investigations in this field. The data was collected and analysed statistically. The results showed that there were significant differences between the pre-test and post-test lipid ratios in type 2 diabetic patients; the proposed programme had a significant impact on improving patients' physical condition.